2003
DOI: 10.1073/pnas.2532677100
|View full text |Cite
|
Sign up to set email alerts
|

Measurements of the concentration and composition of nuclei for cirrus formation

Abstract: This article addresses the need for new data on indirect effects of natural and anthropogenic aerosol particles on atmospheric ice clouds. Simultaneous measurements of the concentration and composition of tropospheric aerosol particles capable of initiating ice in cold (cirrus) clouds are reported. Measurements support that cirrus formation occurs both by heterogeneous nucleation by insoluble particles and homogeneous (spontaneous) freezing of particles containing solutions. Heterogeneous ice nuclei concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

47
482
2

Year Published

2006
2006
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 556 publications
(531 citation statements)
references
References 36 publications
(43 reference statements)
47
482
2
Order By: Relevance
“…The apparent relation of ice nuclei number concentrations to the number concentrations of certain subsets of the atmospheric aerosol has been recognized for more than 40 years (20,(22)(23)(24). All of these studies noted either linear or power law relations between ice nuclei and aerosol number concentrations within restricted size ranges, generally those particles larger than 0.3-μm diameter.…”
Section: Discussionmentioning
confidence: 99%
“…The apparent relation of ice nuclei number concentrations to the number concentrations of certain subsets of the atmospheric aerosol has been recognized for more than 40 years (20,(22)(23)(24). All of these studies noted either linear or power law relations between ice nuclei and aerosol number concentrations within restricted size ranges, generally those particles larger than 0.3-μm diameter.…”
Section: Discussionmentioning
confidence: 99%
“…), cloud internal dynamics (Marsham and Dobbie, 2005;Fusina and Spichtinger, 2010) and background aerosols that are either liquid and freeze homogeneously (Hoyle et al, 2005;Spichtinger and Gierens, 2009a) or contain a solid and may act as heterogeneous ice nuclei (DeMott et al, 2010). Ice in the upper troposphere is known to nucleate via both pathways, homogeneous freezing of aqueous solution droplets (Koop et al, 2000) or heterogeneous nucleation on solid aerosol particles (DeMott et al, 2003). Both mechanisms, and especially homogeneous freezing, require regions with very low temperatures and high supersaturation with respect to ice.…”
Section: A Cirisan Et Al: Balloon-borne Match Measurementsmentioning
confidence: 99%
“…Here we adopted the canonical value of 10 L −1 by DeMott et al (2003). Table 4 lists two heterogeneous scenarios in comparison with other scenarios, while Table C1 shows additional calculations for various IN concentrations (see Appendix C).…”
Section: Heterogeneous Nucleation Of Icementioning
confidence: 99%
“…It has also recently been observed that atmospheric particles with high organic content are not as efficient at ice nucleation (DeMott et al, 2003;Cziczo et al, 2004). The effects that organic compounds have on the ability of particles to nucleate ice has only recently begun to be studied in the laboratory.…”
Section: Introductionmentioning
confidence: 99%
“…The Koop et al (2000) model is also potentially applicable even if aerosols are not in equilibrium with atmospheric water vapor, as long as the aerosol organic content can be determined and related to aerosol water activity. However, field measurements have indicated that mixed organic/sulfate aerosol might be less efficient at ice nucleation (DeMott et al, 2003;Cziczo et al, 2004). One possible explanation for this observation is that the presence of organic compounds modifies the water uptake properties of the aerosol, and serves to sever the equilibrium between aerosol water content and atmospheric water vapor.…”
Section: Introductionmentioning
confidence: 99%